2020
DOI: 10.7124/bc.000a2c
|View full text |Cite
|
Sign up to set email alerts
|

Spirocyclic thienopyrimidines: synthesis, new rearrangements under Vilsmeier conditions and in silico prediction of anticancer activity

Abstract: Aim. To find novel anticancer lead molecules among easily available spiro-fused thieno[2,3-d] pyrimidines. Methods. Organic synthesis, spectral methods and molecular docking. Results. New spiro heterocycles were synthesized by condensation of 2-aminothiophene-3-carbonitriles with cyclic ketones via Gevald reaction. Other model spirocyclic compounds were prepared by the reaction of 3-aminothieno[2,3-b]pyridine-2-carboxamides with cyclohexanone under acidic conditions. According to the docking studies against th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 46 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, this method was applied to 3-imino(thiophen-2-yl)furan-2(3H)-ones derivatives, which include the pharmacophore fragment, Gewald aminothiophene [37][38][39][40][41]. Compounds that contain this pharmacophore fragment exhibit analgesic [42][43][44], anti-inflammatory [45,46], antimicrobial [47][48][49] and photoluminescent properties [50,51] and other biological activities [52][53][54]. Also, we showed that N′-[5-aryl-2-oxofuran-3(2Н)ylidene]furan-2-carbohydrazides and its precursor 4aryl-2-[2-(furan-2-ylcarbonyl)hydrazinylidene] -4oxobutanoic acids have analgesic activity in the previous studies [55].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this method was applied to 3-imino(thiophen-2-yl)furan-2(3H)-ones derivatives, which include the pharmacophore fragment, Gewald aminothiophene [37][38][39][40][41]. Compounds that contain this pharmacophore fragment exhibit analgesic [42][43][44], anti-inflammatory [45,46], antimicrobial [47][48][49] and photoluminescent properties [50,51] and other biological activities [52][53][54]. Also, we showed that N′-[5-aryl-2-oxofuran-3(2Н)ylidene]furan-2-carbohydrazides and its precursor 4aryl-2-[2-(furan-2-ylcarbonyl)hydrazinylidene] -4oxobutanoic acids have analgesic activity in the previous studies [55].…”
Section: Introductionmentioning
confidence: 99%